2021
DOI: 10.1152/ajpregu.00310.2020
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-sweetened soft drink consumption acutely decreases spontaneous baroreflex sensitivity and heart rate variability

Abstract: In healthy humans, fructose-sweetened water consumption increases blood pressure variability (BPV) and decreases spontaneous cardiovagal baroreflex sensitivity (cBRS) and heart rate variability (HRV). However, if consuming commercially available soft drinks containing high levels of fructose elicits similar responses is unknown. We hypothesized that high-fructose corn syrup (HFCS) sweetened soft drink consumption increases BPV and decreases cBRS and HRV to a greater extent compared to artificially-sweetened (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In contrast, Christiani found a smaller effect of hypertonic sugar-sweetened sports drinks than water on resting HRV, despite accompanying glucose disturbances [37]. Chapman reported that consumption of sugar-sweetened soft drinks reduced spontaneous baroreceptor sensitivity and heart rate variability but not blood pressure variability [38]. Other authors have noted that insulin stimulates the low-to high-frequency ratio [LF/HF] in spectral analysis of HRV in both lean and obese individuals, thus indicating a shift from the activity of the cardiac autonomic nervous system toward the predominance of the sympathetic nervous system [39].…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Christiani found a smaller effect of hypertonic sugar-sweetened sports drinks than water on resting HRV, despite accompanying glucose disturbances [37]. Chapman reported that consumption of sugar-sweetened soft drinks reduced spontaneous baroreceptor sensitivity and heart rate variability but not blood pressure variability [38]. Other authors have noted that insulin stimulates the low-to high-frequency ratio [LF/HF] in spectral analysis of HRV in both lean and obese individuals, thus indicating a shift from the activity of the cardiac autonomic nervous system toward the predominance of the sympathetic nervous system [39].…”
Section: Discussionmentioning
confidence: 96%
“…The present study was designed based on the findings of Chapman et al who determined cardiovascular effects of a caffeinated soft drink sweetened with HFCS consumption were caused by HFCS in young healthy adults (Chapman et al, 2019 , 2020 , 2021 ). Thus, we employed the same commercially available caffeinated soft drink sweetened with HFCS utilized previously to test our hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Following the pre‐consumption period, participants were given 5 min to consume 500 ml of water or DEW chilled to about ~11℃, and then resumed the supine position (Figure 1 ). Mountain Dew is a high calorie, high‐fructose, caffeinated soft drink that has previously been demonstrated to cause renal vasoconstriction during rest and sympathetic activation (Chapman et al, 2020 ) and reduce spontaneous cardiovagal baroreflex sensitivity (Chapman et al, 2021 ). Mountain Dew has one of the highest free fructose concentrations among commercially available soft drinks, with fructose and glucose each representing 59.5% and 39.7%, respectively, of the total sugar content of the beverage (Walker et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[104][105][106] Both fructose-sweetened water consumption and HF corn syrup-sweetened soft drink consumption acutely reduced spontaneous baroreflex sensitivity in healthy humans. 35,107 Interestingly, HF intake decreased baroreflex sensitivity within a week (day 1) and induced a progressive reduction in baroreflex sensitivity over time. 104,106 But the alteration of oxidative stress-related markers was found at day 15 or later.…”
Section: Impaired Baroreflex Sensitivity Contributes To Hf-induced Sshmentioning
confidence: 99%